E-@NT: Un Open Archive per la Ricerca Italiana in Antartide - Marchitelli, Andrea; Chiodetti, Anna Grazia (2004)
The Italian National Polar Research Program will create an institutional open archive to collect its scientific production. This paper describe the current situation and display the future.